Первое вторжение монголов в Восточную Европу (1222 г) - Пилипчук, Я.В. (Степи Европы в эпоху средневековья, 2012)
Одним из наиболее значимых событий эпохи средневековья были монгольские завоевания. Традиционными темами мировой историографии является монгольское завоевание Китая, Центральной Азии, Руси, но пока исследователям остается практически неизвестной борьба кыпчаков против завоевателей. Цель данной статьи - освещение первого монгольского вторжения на Северный Кавказ и в Восточную Европу. В центре внимания находится противостояние монголов с кыпчаками. Хотя этот аспект упоминался практически во всех работах, посвященных монгольским завоеваниям и Чингисхану, но почти нигде не был рассмотрен детально. Только некоторые исследователи пробовали реконструировать маршрут монгольского вторжения на Северный Кавказ. This paper is devoted to the debatable issues of the history of the Mongolian invasion of the North Caucasus and Eastern European steppes. The Mongols failed to pass through the Derbent pass and had to surmount the Caucasian mountains in the area of modem Dagestan. On the Terek river they came up against the “Derbent Kypchaks” who did not betray the Alans since they were not their allies in 1222. The tidings of the Persian chroniclers Juvaini and Rashid al-Din about Sarir helping the Georgians to repel Jelal ad-Din’s aggression should be regarded as unreliable. After their victory over the “Derbent Kypchaks” the Mongols attacked the eastern Alans. Then the Mongols’ forces were divided. Subedei- bagatur’s tumen passed through the Sal steppes and reached the Don where it defeated Yuriy Konchakovich’s army. Yuriy Konchakovich himself survived and asked the Ruses for support. Pursuing the Sharukanids, Subedei-bagatur’s tumen reached the Dnieper. Jebe-noion’s tumen continued warfare in the North Caucasus. Through the Terek and the Kuban valleys it reached Matarkha where it defeated the local Adyge, who were known to the Slavs as the Kasogs. In winter of 1222/1223 Jebe-noion’s tumen crossed the Kerch Strait over ice and reached Sudak. After Sudak was captured the Mongolian tumens united again in the steppes of the Azov Sea littoral.